Pascal Functions. Issue 2 (7th February 2018) - Maltenfort, Michael
Abstract: We define Pascal functions by adapting the arithmetic rule that creates the Pascal triangle. By developing and applying properties of Pascal functions, we discover new identities and find new perspectives of old identities. The identities all involve binomial coefficients, with some also involving Stirling numbers, Stirling polynomials, associated Stirling numbers of the second kind, or Bell numbers.